RELASI KUASA DALAM PENGELOLAAN REMITAN TKI DI KECAMATAN JAMBON KABUPATEN PONOROGO (Studi Tentang Perubahan Pengelolaan Remitan TKI ke Sektor Jasa di Kecamatan Jambon Kabupaten Ponorogo) - 105120100111039, Nurul Hidayatul Fitriyani (Jurnal Mahasiswa Sosiologi, 2014)
ABSTRACT Nurul Hidayatul Fitriyani. (2014). Department of Sociology. Faculty of Social and Politics Science. Brawijaya University. Management of Relation Authorization Changes of Remittance of Indonesian Migrant Workers in the Jambon, Ponorogo. Advisors: Iwan Nurhadi, S.Sos., M.Si and Andini Setya Karlina, M.A   The study discusses about the management of remittance changes of migrant worker in Jambon. It aims to comprehend and analyze the economic investment of relation authorization changes conducted by Indonesian Migrant Workers in Jambon into service sector which aims to change the remittance management. In the study, is used to know the management of relation authorization of remittance of Indonesian Migrant Workers in Jambon.  Without relation authorization, the management changes of remittance cannot be realized. It is needed some elements of knowledge and discourse to create relation authorization. The elements are crucial to be used in analyzing the management of relation changes of remittance into service sector.  In addition, the qualitative design through case study approach is used in this study. The result of the study shows that the changes of remittance investment management conducted by Indonesian Migrant Workers into service sector based on knowledge reproduction and discourse of before, during, and after becoming Indonesian Migrant Workers. The practice of power that any form of domination of government and NGO, as a discipline and control apparatus. Kind of Indonesian Migrant Workers discipline in Jambon looks by doing BIMTEK and socialization. Not only that, it’s able to reproduce the Indonesian Migran Workers knowledge after completion of the training organized by government,even the TKI is also given freedom to manage remittance into the desire effort according to the capacity of the knowlwdge; as fotocopy, travel, drawing room, printing office and etc. Keywords : Remittance, Indonesian Migrant Workers in Jambon, Knowledge, Power  and Discourse